2005
DOI: 10.1039/b418870e
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear bis-β-diketonato ligand derivatives of iron(iii) and copper(ii) and use of the latter as components for the assembly of extended metallo-supramolecular structures

Abstract: A range of 1,3-aryl linked, bis-beta-diketone derivatives (LH2) has been employed to synthesise neutral bis(ligand), dinuclear complexes incorporating square-planar copper(II) and tris(ligand) dinuclear helical derivatives containing octahedral iron(III). The 1H NMR spectra of the free ligands contain singlet peaks at ca. 16.2 ppm, indicative of enolic protons, confirming that the (bis) enol tautomer is present in solution. An X-ray structure of a ligand from the series incorporating tert-butyl terminal substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 17 publications
5
72
1
Order By: Relevance
“…2) has five-coordinate copper(II) centres with two planar dinuclear metallocyclic units bridged by two dmpip ligands such that the overall structure is a discrete tetranuclear architecture similar to those previously reported by us using dabco and pyrazine as bridging ligands. 13,20 However, in contrast to these previous structures, the present structure is somewhat 'stepped' resulting from the presence of the chair conformation of the respective bound dmpip ligands. This results in the mean planes of the two dinuclear platforms being separated by 6.35 Å -considerably less than occurs in the tetranuclear analogues incorporating 'linear' dabco (7.73 Å) or pyrazine (7.5 Å) as the bridging co-ligands.…”
Section: Dalton Transactionscontrasting
confidence: 75%
“…2) has five-coordinate copper(II) centres with two planar dinuclear metallocyclic units bridged by two dmpip ligands such that the overall structure is a discrete tetranuclear architecture similar to those previously reported by us using dabco and pyrazine as bridging ligands. 13,20 However, in contrast to these previous structures, the present structure is somewhat 'stepped' resulting from the presence of the chair conformation of the respective bound dmpip ligands. This results in the mean planes of the two dinuclear platforms being separated by 6.35 Å -considerably less than occurs in the tetranuclear analogues incorporating 'linear' dabco (7.73 Å) or pyrazine (7.5 Å) as the bridging co-ligands.…”
Section: Dalton Transactionscontrasting
confidence: 75%
“…Hence the use of an excess of linker might be expected to help promote formation of a prismatic arrangement rather than, for example, the step-like polymer observed for the structure described above and the structure of [Cu 2 (L 1 ) 2 (azpy)] n reported previously. 6 Clearly prismatic arrangements require more linker moieties per triangular building block than occurs in the above stepped polymeric structure, with its 1 : 1 (building block: linker) stoichiometry. In view of this the synthetic procedure outlined for {[Cu 3 (L 2 ) 3 (bipy)(THF)]·2.75THF} n was repeated using excess 4,4 -bipyridine.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the 1,3-aryl linked ligands tend to form dinuclear complexes on interaction with divalent metal ions; as is exemplified by the preparation of the copper(II) 'dimer' complex 1. 5,6 On reaction with trivalent metal ions, the 1,3-linked derivatives have been demonstrated to yield neutral dinuclear triple helical structures 9 while their 1,4-linked analogues yield tetranuclear, tetrahedral-shaped (neutral) products. 7 We have previously demonstrated that 1 can act as a dinuclear building block for the formation of a discrete tetranuclear 'dimer of dimers' on reaction with the ditopic linker unit pyrazine, while a one dimensional coordination polymer of stoichiometry [Cu 2 (L 1 ) 2 (azpy) 2 ] n was obtained when the 'offset' linear linker, 4,4 -trans-azopyridine (azpy) was employed.…”
Section: Introductionmentioning
confidence: 99%
“…4 In prior studies we have shown using X-ray diffraction that neutral species of stoichiometry Cu 2 L 1 2 (solvent) n contain planar Cu 2 L 1 2 units, with tetrahydrofuran or pyridine solvent molecules weakly bound in an axial position on each copper(II) (to yield square pyramidal coordination geometries). 5 In contrast to the situation for copper, the metal ion chemistry of L 1 with other divalent metals has received little attention, although two zinc(II) derivatives of this ligand (with R = Ph) have recently been reported.…”
Section: 1112mentioning
confidence: 99%